Day 2 Tue, October 01, 2019 2019
DOI: 10.2118/196084-ms
|View full text |Cite
|
Sign up to set email alerts
|

State of the Art of Flow Management for Frac Plug Drillout and Flowback

Abstract: Highly efficient multi-stage hydraulic fractured horizontal wellbores are the dominant completion method for many basins worldwide. One potential weakness of multi-stage hydraulic fracturing is that the later stages of the completion workflow – frac-plug drill out (FPDO) and flowback – cause large pressure fluctuations and transient flows through the perforation clusters that coincide with a period of low closure stress in the fractures. The proppant packs in the fractures during this period are fragile and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The authors showed that monitoring flowback with a high-frequency flowmeter was a useful technique for optimizing well productivity during well cleanup. The paper also indicated that the use of a dual-energy gamma-ray multiphase flowmeter equipped with a dual-energy gamma-ray helped quantify the amount of debris produced during FPDO and flowback [12].…”
Section: Current Field Practicesmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors showed that monitoring flowback with a high-frequency flowmeter was a useful technique for optimizing well productivity during well cleanup. The paper also indicated that the use of a dual-energy gamma-ray multiphase flowmeter equipped with a dual-energy gamma-ray helped quantify the amount of debris produced during FPDO and flowback [12].…”
Section: Current Field Practicesmentioning
confidence: 99%
“…Optimum cleaning conditions: pump rate = 4 bpm AV = 258 ft/min for 2-3/8" CT and 5"-casing AV ≥ 200 ft/min for CT sizes 2-3/8" and 2-5/8" and casing sizes 5" and 5.5" [12] Showed that early stage monitoring of flowback with high accuracy meters had proven to be an invaluable technique in optimizing well productivity during clean-up stages. The authors proposed that well construction workflow should be dynamic to enable predicting early well performance issues and account for relationships between various well operations.…”
Section: Authors Study Findingsmentioning
confidence: 99%